Hermeneutic Nuances of Shoe-related Rhetoric in Iraqi Culture - Al-Kaisi, Meis (2025)
Culture is complex and sensitive and due to the heterogeneous nature of the modern civilised world we ought to reflect on these differences to understand the other. Thus, what seems to be acceptable in one culture may be perceived as unconventional and very offensive in another. As Raymond Williams once said in his Keywords (1983) cultures 'just don't speak the same language.' Showing the sole of one's shoe to a fellow human is considered offensive in Arab culture. Although the term 'shoe' does not seem to have a wide semantic range in the West, culturally speaking, on the other hand, in the Arab world, it does, and especially in Iraq. Iraqis seem to have unleashed their linguistic creativity in applying a myriad of meanings to the term 'shoe' that vary according to gender, age, status, context and circumstance. Whether in plural or in singular form, it may be used to amplify or exaggerate, or to offend and insult. Iraqis experience the shoe linguistically but also see it as a flying object and as a "weapon of mass-destruction." Perhaps the most notable "pitcher" in this context is Muntazar al-Zaidi, the journalist, who threw his shoes at George W. Bush during a press conference in Baghdad in 2008 and accompanied that act with a statement saying: 'This is a farewell kiss from the Iraqi people, you dog.' And so, when confronted with a shoe in Iraq, thoughts come to mind, all of which are of negative connotation leading to an incontrovertible conclusion that the sought-after objective is an insult of some kind. This paper attempts to trace the origin of this cultural attitude and the offensive nature of shoes and feet in Iraqi culture. It also seeks to explain the various hermeneutic nuances (literal, moral, allegorical) of such rhetoric in Iraq. The Arabic term qundara ('shoe') is a keyword that symbolically represents a cultural gesture and articulates a linguistic attitude which all Iraqis, and most Arabs, can relate to. Most significantly, this paper aims to deliver a comprehensive record of a cultural keyword as well as a sociolinguistic trend which has yet not been scholarly addressed.